EFFICACY OF CONSERVATIVE MANAGEMENT OF EARLY POST-TRAUMATIC CEREBROSPINAL FLUID RHINORRHEA - Shahbaz Ali Khan; Bilal Ahmad; Sajjad, Muhammad; Mushtaq Ahmed; Arshad Khan; Adil Ahsan; Attiya Nasir Siddique; Abdul Aziz Khan (Journal of Ayub Medical College Abbottabad, 2022)
Background: The incidence of Post-traumatic Cerebrospinal Fluid Rhinorrhoea (PCSFR) has been decreased due to advanced therapeutic measures. The current investigative study has been arranged to assess the efficacy of conservative management of early PCSFR. Methods: This cross-sectional study was conducted at departmental of Neurosurgery, Ayub Medical Institute, Abbottabad. Patients with traumatic brain injury having Cerebrospinal fluid rhinorrhoea with either gender having age 5-50 year and presenting within seven days of traumatic brain injury were included. Moreover, those with nasal fractures, penetrating head injuries having fever and neck stiffness were also included in the study. Results: A total number of 120 patients having male dominancy, i.e., 86 (72%) were included in the study with the mean age of 27 years ± 8.741 in which 77 (92%) patients were in the age range of 2nd to 4th decades. The commonest cause was trauma due to Road Traffic Accidents (RTA) having 65 (54%) patients. Conservative treatment was effective in 62 (52%) patients predominantly in the patients of 3rd decade, i.e., 31 (50%), in which the effectiveness in male gender was revealed to be 52.32% (45) and effectiveness in RTA patients was recorded to be 54.83%. Similarly, the Chi-Square value was calculated for the PCSFR patients for four groups of patients (5-20, 21-30, 31-40, 41-50) to be 48.27 having critical value of 7.81 with the p-value of 1.87e-10, which completely rejects the Null-hypothesis for the patients of various ages. Conclusion: Based on the current investigative study, it may be concluded that PCSFR is common in middle age population with slight male dominancy. It may also be inferred that RTA is the leading cause of PCSFR in our set up and majority of the patients shows improvement after conservative management. Moreover, the effectiveness of conservative management of PCSFR could be predominantly observed in the patients of 3rd decade.